Artificial grassland establishment alters soil organic carbon fractions and cbbL-type carbon-sequestering microbial communities - Shan, Linge; Julihaiti, Aasitaiken; Wang, Wenhao; Lu, Die; Hu, Yi; Zhao, Baolong; He, Yake; Meng, Xiangkang; Yang, Helong (Frontiers in Microbiology, 2025)
IntroductionSoil organic carbon (SOC) dynamics and microbial drivers in arid regions are critical for ecosystem restoration and carbon sequestration. This study investigated how converting cropland to artificial grasslands influences SOC fractions and the community of carbon-fixing microorganisms in the arid region of Urumqi, Xinjiang, China.MethodsWe established two types of artificial grasslands—grassy (GG) and leguminous (LG)—and compared them against adjacent cropland (CK). We analyzed SOC fractions, including particulate organic carbon (POC) and mineral-associated organic carbon (MAOC), and measured cumulative carbon mineralization. The abundance of the cbbL gene was quantified by quantitative PCR. The composition of the cbbL-harboring microbial community was characterized by sequencing the cbbL gene amplicons.ResultsThe MAOC content was significantly higher in GG than in CK and LG. Although the proportion of POC was higher in CK, its absolute content was lowest in LG. Cumulative carbon mineralization was significantly lower in CK than in GG and LG. The cbbL gene abundance was highest in LG. A total of 47,026 cbbL gene amplicon sequence variants were identified, predominantly from Proteobacteria and Actinobacteria, with facultative autotrophs as the dominant functional group. Compared to CK, both grassland types increased the relative abundance of Actinobacteria but decreased that of Planctomycetes. At the genus level, LG significantly enriched SinoRhizobium and MesoRhizobium, whereas GG promoted Microvirga and Bradyrhizobium.DiscussionMantel tests identified soil pH, the proportions of soil aggregates (>2 mm, 2–0.25 mm, and <0.053 mm), electrical conductivity, and MAOC content as the key environmental factors shaping the carbon-fixing microbial community. These results demonstrate that the establishment of artificial grasslands, particularly leguminous types, enhances the potential for soil carbon sequestration by modulating key soil properties and enriching specific carbon-fixing microbial taxa. This study provides a scientific basis for using artificial grasslands to enhance ecological restoration and soil carbon sequestration in arid regions.